Pengungkapan Islamic Social Reporting : Studi Empiris Pada Bank Umum Syariah - Puspasari, Amelia; Muzakki, Muzakki (LP2M IAI Miftahul Ulum Pamekasan, 2021)
This study aims to investigate the factors that influence the disclosure of Islamic social reporting. Some of these factors are profitability, leverage, and liquidity. This study uses a quantitative study with multiple linear regression analysis techniques. The sampling technique used was purposive sampling or judgment sampling, with a sample of 55 taken from 10 Islamic commercial banks that have been registered with Bank Indonesia (BI) and have annual reports for 2014-2018. This study found that the performance variables measured by ROA, liquidity as measured by FDR, and bank risk as measured by NPF had a positive effect on the variable CSR disclosure as measured by the ISR. Company size and age have a negative effect on CSR disclosure as measured by the ISR. Meanwhile, performance variables as measured by ROA, liquidity as measured by FDR, and company size or Size have a significant effect on CSR disclosure as measured by ISR, while NPF bank risk and company age as measured by AGE has no significant effect on ISR.